The Hub : Norm Garlie with Doug Vicars and Rosemary McDonald - Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. Division of Educational Technology, 1977)
Norm Garlie interviews Doug Vicars and Rosemary McDonald about The HUB (the Physically Handicapped Service Centre), a centre in St. John's, N.L. that provides social, vocational, and recreational services to people with physical disabilities.